Computational Analysis of the Effects of Antineoplastic Agents on Axonal Transport - Yoshio Goshima; Hiroshi Usui; Takahito Shiozawa; Tomonobu Hida; Satoshi Kuraoka; Sayumi Takeshita; Naoya Yamashita; Yasushi Ichikawa; Yoshinori Kamiya; Takahisa Gotoh; Toshiyuki Gotoh (Elsevier, 2010)
Axonal transport plays a crucial role in neuronal morphogenesis, survival, and function. Despite its importance, however, the molecular mechanisms of axonal transport remain mostly unknown because a simple and quantitative assay system for axonal transport has been lacking. In order to better characterize the molecular mechanisms involved in axonal transport, we here developed a computer-assisted monitoring system. Using lipophilic fluorochrome chloromethylbenzamido dialkylcarbocyanine (CM-DiI) as a labeling dye, we have successfully labeled membranous organelles in cultured chick dorsal root ganglia neurons. We confirmed that sodium azide, an ATPase inhibitor, and nocodazole, a microtubule-destabilizing agent, markedly suppressed anterograde and retrograde axonal transport of CM-DiI-labeled particles. We further tested the effects of several anti-neoplastic drugs on axonal transport. Paclitaxel, vincristine, cisplatin, and oxaliplatin, all of which are known to be neurotoxic and to cause neurological symptoms, suppressed anterograde and retrograde axonal transport. Another series of anti-neoplastic drugs, including methotrexate and 5-fluorouracil, did not affect the axonal transport. This is the first report of an automated monitoring system for axonal transport. This system will be useful for toxicity assays, characterizing axonal transport, or screening drugs that may modify neuronal functions. Keywords:: axonal transport, automated system, chloromethylbenzamido dialkylcarbocyanine (CM-DiI), anti-cancer drug, dorsal root ganglia